The аssessment of the quality of life of gynecological patients - M. A. Kiyok; G. V. Dolgov (Сибирский научный медицинский журнал, 2022)
Quality of Life (QOL) research in Healthcare Service practice is of great importance in various fields of medicine. The assessment of QOL is carried out not only for the analysis of statistics, but also with the aim of improving and optimizing medical organizations activities, developing and standardizing of treatment guidelines, studying the effectiveness of treatment methods in QOL measurements, examining new treatment methods, identifying risk groups for diseases and promotion of preventive measures. A review of the literature dealing with the main modern methods for studying the QOL of patients is presented. Special aspects of the application of methods for assessing the QOL of patients depending on diseases and their role in the study of the effectiveness of treatment are considered. The issues of studying the QOL of patients in gynecological practice are clarified. The paper presents studies estimating the QOL of patients with various gynecological pathologies: uterine myoma, pelvic organ prolapse, endometriosis, climacteric syndrome. Despite the high prevalence of gynecological diseases among the population, currently there is a limited number of developed specific questionnaires on gynecological nosologies. The analysis of the available literature showed that the assessment of the QOL of patients in gynecology was done mainly after surgical treatment. QOL of outpatient clinic patients was assessed only in some studies.